Cattle plague vaccine ready - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Cameroon's National Veterinary Laboratory (LANAVET), which was established in 1985, is now able to provide vaccines against cattle plague to ACP countries as part of the tender programme financed by the EEC. For more details, contact: LANAVET...